2018
DOI: 10.1177/0896920518820934
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Consent in Venezuela: Media Misreporting of a Country, 1998–2014

Abstract: This article assesses Western news media coverage of Venezuela between 1998 and 2014. It found that the major newspapers in the UK and US reproduce the ideology of Western governments, ignoring strong empirical evidence challenging those positions. The press portrayed Venezuela in an overwhelmingly negative light, presenting highly contested minority opinions as facts while barely mentioning competing arguments, as Herman and Chomsky’s (2002) propaganda model would predict. After conducting interviews, it is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…He now plays by the liberal democratic rules and can therefore be treated as an odd but legitimate political actor, less controversial than his leftist homologues in Cuba or Venezuela. In the end, this reinforces rather than refutes the claims made in previous research about the centrality of a liberal democratic framework for the ascription of legitimacy in mediated representations about Latin America (see Abalo 2015;Lewis 2016;MacLeod 2018).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…He now plays by the liberal democratic rules and can therefore be treated as an odd but legitimate political actor, less controversial than his leftist homologues in Cuba or Venezuela. In the end, this reinforces rather than refutes the claims made in previous research about the centrality of a liberal democratic framework for the ascription of legitimacy in mediated representations about Latin America (see Abalo 2015;Lewis 2016;MacLeod 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Previous research on international journalism about Latin America has shown that liberal democratic ideals are important parameters for ascribing positive and negative characteristics to the social actors represented (Abalo 2015;Lewis 2016;MacLeod 2018). Deviance from such ideals is likely to lead to negative representations.…”
Section: Distancing Difference: Dealing With Mujica's Pastmentioning
confidence: 99%
“…Further, some scholarly attention was paid to support and oppose elections in allied and non-allied regimes of the U.S. (MacLeod, 2018;2019;Chomsky, 1988, 2002). Most importantly, assessing the western media performance, in general, and the U.S. mainstream media specifically, regarding U.S. foreign policies of diplomacy (i.e., statehood recognition) has almost not been devoted.…”
mentioning
confidence: 99%